Comparative analysis of Kotlin and Java languages used to create applications for the Android system - Sulowski, Daniel; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2019)
This publication presents the results of a comparative analysis of Java and Kotlin programming languages used to create mobile applications for system Android. The analysis covers performance aspects such as CPU load, RAM load, as well as the compilation and execution times. Aspects such as code structure, availability of libraries, supported databases, popularity and community support were taken under consolidation.